Exploring Pronouncing English Sounds : Book Review For Japanese Language Learners - Azkiyah, Hayatul (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractA book review is an analytical description and analysis of a work of literature that evaluates the work's merits and shortcomings in terms of plot, style, and substance. The purpose of this study was to investigate how Japanese speakers pronounce the English language. 'English Pronunciation, Intonation, and Accent Reduction for Japanese Speakers' was written by Peggy Tharpe, M.A. TESOL, in 2021. In this book, she discusses the unique challenges that students face while learning a second language and offers advice on overcoming them. This study reviewed a book on methods for teaching English pronunciation using the library research approach. The writer employed data reduction techniques, including summarizing, highlighting key points, and focusing on basics to prepare the data for analysis. Then, based on the available data, which mostly consists of recorded materials, the writer presented the findings and drew conclusions. According to the results, this book is a valuable resource for those looking to teach or improve their students' English pronunciation, intonation, and accent reduction. This suggests that it was designed with native Japanese speakers in mind and may not be as effective for students of other languages. Those unfamiliar with phonetics or linguistics may find this book to be very technical. Thus, the statistics suggest that this book is a good choice for students learning English pronunciation.Keywords: book review, pronunciation, english soundsAbstrak Resensi buku merupakan uraian analitis dan analisis suatu karya sastra dengan mempertimbangkan kelebihan dan kekurangan karya tersebut dari segi alur, gaya, dan substansi. Tujuan dari penelitian ini adalah untuk menyelidiki bagaimana penutur bahasa Jepang mengucapkan bahasa Inggris. Pengucapan, Intonasi, dan Pengurangan Aksen Bahasa Inggris untuk Penutur Bahasa Jepang ditulis oleh Peggy Tharpe M.A. TESOL, 2021. Di dalamnya, ia membahas tantangan unik yang dihadapi siswa saat mempelajari bahasa kedua dan menawarkan saran tentang cara mengatasinya. Penelitian ini mengulas buku tentang metode pengajaran pengucapan bahasa Inggris dengan menggunakan pendekatan penelitian perpustakaan. Penulis menggunakan teknik reduksi data termasuk merangkum, memilih poin, dan berkonsentrasi pada hal-hal mendasar agar data siap untuk dianalisis. Kemudian berdasarkan data yang tersedia yang sebagian besar berupa materi rekaman, penulis menggunakan penyajian data dan menarik kesimpulan. Hasilnya, buku ini adalah sumber yang bagus bagi mereka yang ingin mengajar atau meningkatkan pengucapan, intonasi, dan pengurangan aksen bahasa Inggris siswanya. Hal ini menunjukkan bahwa ini dibuat dengan mempertimbangkan penutur asli bahasa Jepang dan mungkin tidak berfungsi dengan baik untuk pelajar bahasa lain. Mereka yang tidak terbiasa dengan fonetik atau linguistik mungkin menganggap buku ini sangat teknis. Oleh karena itu, statistik menunjukkan bahwa buku ini adalah pilihan yang baik bagi siswa yang belajar pengucapan bahasa Inggris.Kata kunci: resensi buku, pengucapan, bunyi bahasa inggris